2007
DOI: 10.1097/yic.0b013e3281e2c84b
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind, placebo-controlled trial of desvenlafaxine succinate in the treatment of major depressive disorder

Abstract: The antidepressant efficacy and safety of desvenlafaxine succinate (desvenlafaxine) were evaluated in a phase III, double-blind, placebo-controlled study. Outpatients with a primary diagnosis of major depressive disorder were treated with fixed once-daily doses of desvenlafaxine 200 or 400 mg for 8 weeks. The primary efficacy measure was change from baseline on the 17-item Hamilton Rating Scale for Depression. At the final on-therapy evaluation, adjusted mean change from baseline in 17-item Hamilton Rating Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 14 publications
1
43
0
Order By: Relevance
“…The 5-HT2 blockade mechanism is thought to prevent serotonin-mediated adverse effects on sexual function. On the basis of this it is claimed that in comparison to SSRIs and ven afaxine, mirtazapine is significantly less likely to produce sexual dysfunction [34][35][36]. Ozmenler et al [37] also reported that when remitted patients with SSRI-induced sexual dysfunction were switched to mirtazapine, approximately half of them reported no sexual dysfunction at the end of the 8-week treatment.…”
Section: Role Of Agents With Dual Actions On Serotonin and Norepinephmentioning
confidence: 99%
“…The 5-HT2 blockade mechanism is thought to prevent serotonin-mediated adverse effects on sexual function. On the basis of this it is claimed that in comparison to SSRIs and ven afaxine, mirtazapine is significantly less likely to produce sexual dysfunction [34][35][36]. Ozmenler et al [37] also reported that when remitted patients with SSRI-induced sexual dysfunction were switched to mirtazapine, approximately half of them reported no sexual dysfunction at the end of the 8-week treatment.…”
Section: Role Of Agents With Dual Actions On Serotonin and Norepinephmentioning
confidence: 99%
“…In the second trial by by Septien-Velez and colleagues, 31 375 patients were randomized to receive DVS 200 or 400 mg/day, or placebo. Patients assigned to the 400 mg/day dose, had a 1-week escalation period.…”
Section: Dvs Trials In Doses Of 100 Mg/day and Highermentioning
confidence: 99%
“…The initial dose fi nding trials examined doses of 100, 200 or 400 mg/day, [31][32][33] while subsequent trials evaluated daily doses of 50 and 100 mg. 34,35 Of 5 individual published clinical trials, 4 had a similar fi xed-dose design while 1 was a fl exible dose study.…”
Section: Clinical Trial Designmentioning
confidence: 99%
See 2 more Smart Citations